Autism as early neurodevelopmental disorder: evidence for an sAPPα-mediated anabolic pathway - Lahiri, Debomoy K.; Sokol, Deborah K.; Erickson, Craig; Ray, Balmiki; Ho, Chang Y.; Maloney, Bryan (Frontiers in Cellular Neuroscience, 2013)
Autism is a neurodevelopmental disorder marked by social skills and communication deficits and interfering repetitive behavior. Intellectual disability often accompanies autism. In addition to behavioral deficits, autism is characterized by neuropathology and brain overgrowth. Increased intracranial volume often accompanies this brain growth. We have found that the Alzheimer’s disease (AD) associated amyloid-β precursor protein (APP), especially its neuroprotective processing product, secreted APP α, is elevated in persons with autism. This has led to the “anabolic hypothesis” of autism etiology, in which neuronal overgrowth in the brain results in interneuronal misconnections that may underlie multiple autism symptoms. We review the contribution of research in brain volume and of APP to the anabolic hypothesis, and relate APP to other proteins and pathways that have already been directly associated with autism, such as fragile X mental retardation protein, Ras small GTPase/extracellular signal-regulated kinase, and phosphoinositide 3 kinase/protein kinase B/mammalian target of rapamycin. We also present additional evidence of magnetic resonance imaging intracranial measurements in favor of the anabolic hypothesis. Finally, since it appears that APP’s involvement in autism is part of a multi-partner network, we extend this concept into the inherently interactive realm of epigenetics. We speculate that the underlying molecular abnormalities that influence APP’s contribution to autism are epigenetic markers overlaid onto potentially vulnerable gene sequences due to environmental influence.